2018
DOI: 10.4149/neo_2018_161019n487
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference-mediated silencing of aquaporin (AQP)-5 hinders angiogenesis of colorectal tumor by suppressing the production of vascular endothelial growth factor

Abstract: Aquaporin (AQP)-5 is an essential member of AQP family involved in the tumorigenesis of various malignant tumors. However, its role in the angiogenesis of colorectal cancer is unclear and requires further investigation. In this study, a pRNA-H1.1 vector containing the short hairpin RNA (shRNA) targeting AQP5 mRNA was constructed to inhibit the endogenous expression of AQP5 in human umbilical vein endothelial cells (HUVECs). We found that the AQP5-silenced HUVECs acquired decreased proliferation, migration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…Inhibition of AQP5 significantly decreases the expression of VEGF, which is critical in tumour angiogenesis, suggesting that increased expression of VEGF is positively associated with angiogenesis (21). In a previous study, AQP5 downregulation in colorectal cancer cells resulted in decreased expression of VEGF and a corresponding inhibition of angiogenesis in HUVEC (35). In line with this previous study, the present study found that supernatant collected from H1299 cells following AQP5 knockdown exhibited reduced HUVEC angiogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…Inhibition of AQP5 significantly decreases the expression of VEGF, which is critical in tumour angiogenesis, suggesting that increased expression of VEGF is positively associated with angiogenesis (21). In a previous study, AQP5 downregulation in colorectal cancer cells resulted in decreased expression of VEGF and a corresponding inhibition of angiogenesis in HUVEC (35). In line with this previous study, the present study found that supernatant collected from H1299 cells following AQP5 knockdown exhibited reduced HUVEC angiogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…AQP6 reduction by esiRNA treatment was found to suppress MPM cancer proliferation by about 50%. Similar results have been reported on the reduced proliferation of cancer cell lines by silencing the peroxiporins AQP3, AQP5, and AQP8 [ 62 , 63 , 64 ]. Furthermore, the conditions of oxidative stress, similar to those that occur as a result of the treatment with common chemotherapy treatments, were able to further reduce proliferation, especially in mesothelioma cells.…”
Section: Discussionsupporting
confidence: 88%
“…A similar report revealed that downregulation of AQP5 inhibited hepatocellular carcinoma cell invasion and EMT process through modulating EMT-related molecules, such as E-cadherin and N-cadherin (34). Wang et al (35) reported that AQP5 silencing inhibited proliferation, migration and the enzyme activity of MMP-9 in human umbilical vein endothelial cells, but did not affect the enzyme activity of MMP-2. The discrepancy between this previous report and the current study with regards to MMP-2 may have resulted from different detection indexes (i.e.…”
Section: Discussionmentioning
confidence: 85%